NS2A V89F mutation in a DENV1 clinical isolate enhances neurotropism and neuroinvasion - Yuqi Zhao; Linqing Wang; Yifan Lin; Yangyang Chen; Yan Zhan; Kexin Xi; Yingfang Liu; Chenguang Shen; Bao Zhang; Weiwei Xiao; Qinghua Wu; Li Zhu; et al. (Frontiers in Cellular and Infection Microbiology, 2026)
Introduction Dengue virus (DENV) neurological complications are increasingly reported, yet the viral genetic determinants of neurotropism remain poorly characterized. Methods We screened 25 DENV1 clinical isolates from the 2014 outbreak in Guangdong, China, for neurotropism in suckling mice, and integrated comparative genomics, pre-expression functional assays, population-scale sequence analysis, and OpenFold3 structural modeling to identify mutations associated with enhanced neuroinvasion. Results We found that only strain P1253 induced neurological symptoms and mortality via subcutaneous inoculation, producing cortical-selective lesions distinct from the diffuse encephalitic damage observed after intracranial inoculation, and P1253 replicated preferentially in human brain microvascular endothelial cells (HBMEC) compared to contemporaneous strains. Comparative genomics identified three unique mutations in P1253 (NS1 175Y→H, NS2A 89V→F, NS4A 2V→I), and pre-expression assays demonstrated that only NS2A 89V→F significantly enhanced viral replication and cytopathic effect in HBMEC. Analysis of 1,990 complete DENV1 genomes revealed five natural mutant types in the NS2A 89 -96 residue region, with P1253 representing the FIPI quadruple-mutant type, and OpenFold3 structural prediction showed that 89V→F introduced on the VIPI background induced the most significant distal domain reorientation (RMSD 1.605 Å), increasing the centroid-to-centroid distance between residues 89 -96 and 185 -218 from 18.221 Å to 27.462 Å. Discussion These findings identify NS2A 89V→F as a candidate adaptive mutation associated with enhanced neurotropism in DENV1 and provide a framework for monitoring neurovirulent variants.